SEDIAAN MUKOADESIF MIKROPARTIKEL AMOKSISILIN DENGAN MATRIK KITOSAN TERTIOLASI YANG DIAKTIVASI EDAC HCL - , Azis Ikhsanudin, Prof. Dr. Achmad Fudholi, DEA., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of natural polymer as a drug matrix could enhance the drug therapy effect. One of the prospective natural polymer which can be developed as a drug matrix was chitosan. The modification method of chitosan structure with thiolate reaction could improve the mucoadhesive properties. This study was aimed to formulate and to evaluate the characteristics of mucoadhesive form of amoxicillin trihydrate microparticles with matrix - chitosan thiolate. Thiolated chitosan was prepared by reacting the chitosan as a carrier with cysteine thiol groups by using 1-ethyl-3-(3-dimethylamino propyl) carbodiimide (EDAC) catalyst and was formulated with amoxicillin trihydrate and sodium tripolyphosphat (STPP) to form the microparticles. Amoxicillin trihydrate microparticles were evaluated and characterized by using infrared spectrophotometer and the drug release was tested by using a type II dissolution test (paddle). The results showed that the variation of the EDAC addition as a catalyst will affect the formation of thiol groups, where the formula with 50 mM EDAC has the highest number of thiol group (134.35 Â± 3.56 Î¼mol per 50 mg of chitosancysteine thiolated) and has the most powerful mucoadhesive properties (8, 10 Â± 0.17 hours). The adding of EDAC concentration can affect the characteristics, properties of chitosan-cysteine thiolated such as the physical properties like transparant gel, fibrous solid form, yellowish color, soluble in water and acid, high viscosity, increasing in the swelling behaviour and mucoadhesive properties. The amoxicillin trihydrate release profiles of polymer chitosan-cysteine thiolated showed that the addition of EDAC concentrations in formula may prolong the release of amoxicillin trihydrate.